Comparison of polyunsaturated fatty acid and fat-soluble vitamins content of cooked Shad (Alosa immaculata) - Merdzhanova, A.; Dobreva, D. A; Makedonski, L. (International Journal of Agricultural Technology, 2016)
This study presents the evaluation of the effect of cooking (steaming and grilling) on lipids, fatty acids profile, nutritional quality indices (NQI) and fat soluble vitamins content of Black Sea shad (Alosa immaculata). The Bligh and Dyer’s method was used for total lipid content determination. The fatty acid methyl esters were analysed by GC/MS and fat soluble vitamins - by RP-HPLC. The two cooking methods increased the levels of the saturated fatty acids (SFA), whereas grilling process decreased monounsaturated fatty acids (MUFA) quantity in shad tissue. Omega-3 polyunsaturated FAs (n-3 PUFA) levels significantly decreased after both thermal processes. Steaming doesn’t affect the omega-6 (n-6) PUFA – their amounts remain almost unchanged. The vitamin A value decreases significantly after steaming, whereas vitamin D3 and E remain almost unchanged. Among the three fat soluble vitamins, the grilling process affects significantly mainly vitamin A and E. In conclusion - both cooking methods are suitable for preserving the lipid nutrition quality of shad edible tissue.